Isolation of human antigen‐specific regulatory T cells with high suppressive function. Issue 9 (8th August 2014) - Noyan, Fatih; Lee, Young‐Seon; Zimmermann, Katharina; Hardtke‐Wolenski, Matthias; Taubert, Richard; Warnecke, Gregor; Knoefel, Ann‐Kathrin; Schulde, Elvira; Olek, Sven; Manns, Michael P.; Jaeckel, Elmar
<x xml:space="preserve">Abstract</x> Adoptive transfer of regulatory T (Treg) cells could be an alternative to chronic immunosuppression for prevention of allogeneic graft rejection. While polyspecific Treg cells can prevent immune responses under lymphopenic conditions, Ag‐specific Treg cells are needed to treat autoimmunity and graft rejection. Yet, reliable markers for Ag‐specific Treg cells are missing. We report that latency‐associated peptide (LAP) and glycoprotein A repetitions predominant (GARP) can identify human Ag‐specific Treg cells. In addition, we show that the depletion of CD154+ cells from LAP+ or GARP+ Treg cells increases the Treg‐cell purity to over 90%, as assessed by epigenetic analysis. These Ag‐specific Treg cells can be isolated magnetically and might contribute to the development of GMP‐based protocols. In addition, Ag‐specific Treg cells are functionally far superior to CD4+CD25high or CD4+CD25highCD127low Treg cells in vitro and in preventing strong alloreactions in humanized mice. They could, therefore, have a high therapeutic potential for the control of alloimmune, autoimmune, and allergic immune responses in patients.